THE EFFECT OF SUPPORT PROGRAMS ON ACADEMIC RESILIENCE IN DROPOUT STUDENTS: A SYSTEMATIC LITERATURE REVIEW - Fahsadila, Syehans (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2025)
This study aims to explore the relationship between fulfillment of basic psychological needs, academic resilience, and student success in facing academic challenges. Using a Systematic Literature Review (SLR) approach, this research analyzes various studies that address factors that influence students' academic resilience, including growth mindset, social support, and learning environment. The results show that students with a growth mindset tend to be more resilient, as they see failure as an opportunity to learn and are able to cope with academic stress and pressure. In addition, support from family and school environment play an important role in strengthening students' resilience capacity, helping them overcome the challenges they face. The study also identified limitations, such as the limited sample size and uncontrolled external variables, which may affect the generalizability of the results. The findings emphasize the importance of creating a supportive learning environment and appropriate interventions to enhance students' academic resilience. As such, this study provides valuable insights for educators and policy makers in designing effective strategies to support students in achieving academic success amidst various complex challenges. Keywords: academic resilience, growth mindset, social support, basic psychological needs, education.